Pengaruh Modal Kerja, Tenaga Kerja, Dan Pengalaman (Lama Kerja) Terhadap Pendapatan Nelayan Bagang Tancap Di Kabupaten Tanah Bumbu (Studi Kasus Desa Wirittasi Kecamatan Kusan Hilir) - Nor Amelia; Ali Wardhana (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This study examines the influence of (1) the application effect of working capital,labor, and Experience (light of working) to together toward income in Wirittasi Village,Kusan Hilir Sub District, Tanah Bumbu District (2) the most dominant factor affecting theincome of baggage tancap fishers in the Village Wirittasi, Kusan Hilir Sub District, TanahBumbu District.Data collected from 41 shipowners and Bagang in Village Wirittasi, Kusan HilirSubdistrict, Tanah Bumbu District. Multiple regression analysis with help software SPSSis version 16.The results showed that jointly the cost factor of care, working capital, labor, andexperience (light of working) affects bagang tancap fishers in Wirittasi Village, Kusan HilirSubdistrict, Tanah Bumbu District. Variable Labor (X2) is the factor that has the mostdominant influence on the income of bagang tancap fishers in the Village WirittasiSubdistrict Kusan Hilir Tanah Bumbu District.